Metrology, standardisation and certification study aid - Kim, A. B. specialist in the field of mechanical engineering Senior lecturer of Tomsk Polytechnic University 1980- (Tomsk Polytechnic University Publishing House, 2014)
This book is devoted to dimensional and geometrical tolerancing principles, standardisation and certification aspects and measurement instruments applied in mechanical and manufacturing engineering. The material of this book is written in accordance with the relevant state standards of Russian Federation.The book is recommended for English-speaking students following the Bachelor Degree Program in Mechanical Engineering at Tomsk Polytechnic University.